A Micro Structure in Setya Novanto’s Meme on Social Media - Khodijah, Siti (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
This research analyzed the lexical style employed in Setyo Novanto's memes, which have gained widespread circulation on various social media platforms. In order to attain this goal, the study employs van Dijk's theory, which identifies lexical style as a crucial component of the microstructure of memes on social media. The primary aim of this study is to describe the words and expressions utilized to insinuate and criticize Setyo Novanto's conduct. This research was qualitative and delves into the internal structure of the text, including words, phrases, propositions, and sentences. The analysis revealed that writers from diverse cultural, knowledge, and ideological backgrounds used specific lexical to scrutinize Setyo Novanto's behavior in relation to his status. This study provided valuable insights into how social media users employed language to express their opinions and criticisms of public figures. Overall, this research was highly informative in terms of shedding light on the way social media users utilized language to express their opinions and criticisms of public figures.